ZnO nanoparticles filled tetrapod-shaped carbon shell for lithium-sulfur batteries. (January 2019) - Yang, Rongliang; Du, Huiwei; Lin, Zhiqiang; Yang, Leilei; Zhu, Hai; Zhang, Hao; Tang, Zikang; Gui, Xuchun
Abstract: Employ of hollow nanostructure carbon materials as a host framework for sulfur cathode is a promising strategy to cope with the notorious posers in lithium-sulfur (LiS) battery. However, the dissolution and diffusion of intermediate polysulfides in electrolytes still result in rapid capacity loss and poor rate performances, due to the weak interaction between polarized lithium polysulfides and non-polarized carbon host. To address this challenge, a bipolar material, zinc oxide embedded tetrapod-shaped carbon shell (TCS/ZnO) is designed for polysulfides immobilization in LiS battery. The TCS/ZnO composites are synthesized through a CVD process using tetrapod shaped ZnO nanowhiskers as template, following by a partially hydrogen etching treatment. Attributed to the strong chemisorption of ZnO to polysulfides, high initial specific capacity of 1284 mAh g −1 sulfur, stable Coulombic efficiency of ∼99.5% and excellent cycling stability (815 mAh g −1 sulfur after 100 cycles at 0.2 C) are exhibited for S-TCS/ZnO cathode with optimized ratio of ZnO. Graphical abstract: Image 1